Pengaruh Profitabilitas, Kondisi Keuangan, dan Reputasi Auditor terhadap Audit Delay: Studi Kasus pada Perusahaan BUMN yang terdaftar di Bursa Efek Indonesia - Rama Praja Setia; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to identify whether there is a correlation between auditor reputation, financial condition, and profitability with audit delay. The subjects of this study were state-owned companies traded on the Indonesia Stock Exchange between 2019 and 2023. A total of 135 samples were taken from 27 different companies for 5 years. The sample selection technique used a purposive sampling approach. The research instrument used to test the hypothesis was SPSS version 20 which used the multiple regression method. The results of the study indicate that audit delay is not affected by profitability, financial condition and auditor reputation. Simultaneously, auditor reputation, financial condition, and profitability affect audit delay. Other variables that affect audit delay that are not considered in this study are anticipated to be used in future research.